Gender Determinant on Multidimensional Poverty Index: Evidence from Indonesia - Thomas Soseco; Isnawati Hidayah; Ayu Dwidyah Rini (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2022)
Poverty measurement from a non-monetary aspect is needed as low-income individuals are not always multidimensionally poor, and vice versa. The focus should also be on the gender determinant potentially related to the inequality in wage, labour market, and the return of education, which can influence the household’s ability to achieve a higher standard of living and alleviate poverty. This paper discovers the contribution of gender determinants to multidimensional poverty conditions in Indonesia. This paper used logit estimation using National Socioeconomics Survey (Susenas) 2018. The data show that approximately 10% of the Indonesian population is considered vulnerably poor, and severely poor is 3%. The vulnerably and severely poor individuals are mostly measured from years of schooling, health insurance ownership, and assets ownership. Moreover, we find that variables of household size, dependency ratio, and household head age are the better explanators of poverty’s vulnerability. However, those variables cannot explain severe poverty among female- and male-headed households, even though female-headed households are more prone to falling into poverty situations. Then, the decomposition results show that our selected variables explain the probability of being vulnerable poor. However, the probability of being severely poor is largely determined by unobservable behaviour domination not included in the study.